(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The featured item showcases a square, reconfigurable antenna with dimensions of 20 x 35 x 0.8 mm³, featuring four corner slots on the patch. These slots introduce additional modes that lend themselves to circular polarization. The transition between Linear Polarization (LP) and Circular Polarization (CP) is facilitated through a PIN diode situated within an L-shaped slot within the ground plane. The antenna design has undergone optimization and thorough analysis through simulations. The 3 dB axial ratio bandwidth and the -10 dB impedance bandwidth share a frequency range from 5.15 to 6.25 GHz, covering 19.3% of the spectrum. This prototype antenna has been subjected to testing in both forward and reverse polarization configurations. The operational frequency band encompasses the WLAN band, as defined by IEEE 802.11a (5150 - 5350 MHz, 5725 - 5825 MHz), and the HIPERLAN band (5450 - 5725 MHz). This frequency range aligns well with the balance observed between simulated and tested results. The antenna’s omnidirectional radiation patterns make it particularly well-suited for use in portable wireless medical devices.